2022
DOI: 10.1038/s41556-022-00899-8
|View full text |Cite
|
Sign up to set email alerts
|

Migratory and anti-fibrotic programmes define the regenerative potential of human cardiac progenitors

Abstract: Heart regeneration is an unmet clinical need, hampered by limited renewal of adult cardiomyocytes and fibrotic scarring. Pluripotent stem cell-based strategies are emerging, but unravelling cellular dynamics of host–graft crosstalk remains elusive. Here, by combining lineage tracing and single-cell transcriptomics in injured non-human primate heart biomimics, we uncover the coordinated action modes of human progenitor-mediated muscle repair. Chemoattraction via CXCL12/CXCR4 directs cellular migration to injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…In addition to cell‐based therapy, there are cell‐free strategies, such as EVs and exosomes. Studies have illustrated that EVs derived from various stem cells harbour the ability of cardioprotection when delivered in murine models of MI 50,51 or HF 52,53 . Our findings confirm that CPPs exert reparative functions through CPPs‐Exo, as blocking exosome release abrogated the functional recovery achieved by delivery of CPPs into the ischemic area of the murine heart.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to cell‐based therapy, there are cell‐free strategies, such as EVs and exosomes. Studies have illustrated that EVs derived from various stem cells harbour the ability of cardioprotection when delivered in murine models of MI 50,51 or HF 52,53 . Our findings confirm that CPPs exert reparative functions through CPPs‐Exo, as blocking exosome release abrogated the functional recovery achieved by delivery of CPPs into the ischemic area of the murine heart.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have illustrated that EVs derived from various stem cells harbour the ability of cardioprotection when delivered in murine models of MI 50,51 or HF. 52,53 Our findings confirm that CPPs exert reparative functions through CPPs-Exo, as blocking exosome release abrogated the functional recovery achieved by delivery of CPPs into the ischemic area of the murine heart. Moreover, CPPs-Exo delivery at the early phase of MI recapitulates the beneficial effects of their parent cells in the treatment of MI.…”
Section: Discussionsupporting
confidence: 70%
“…A previous in silico study showed that the risk of spontaneous hPSC-CM beats increases with higher hPSC-CM density, larger hPSC-CM clustering and injection proximal rather than distal to the infarct (Yu et al, 2019). In our study, we modelled the spatial distribution of hPSC-CM based on experimental observations from (Poch et al, 2022), rather than varying density, clustering and injection locations. Therefore, although the number of delivered cells relative to the scar size was maintained in our study, absolute cell number, density and clustering varied between the different scar geometries.…”
Section: Discussionmentioning
confidence: 99%
“…Existing adult ventricular cells (ToR-ORd model) were randomly replaced by the hPSC-CMs (Paci model), with probabilities depending on infarct versus border zone, transmurality and distance to the nearest delivery location (see supplementary Table S4 for further detail). Probabilities were calibrated using experimental insights from (Poch et al, 2022), where in non-human primate tissue slabs, more injected cells settled in the infarct core compared to the border zone. Informed by Poch et al’s in vivo porcine models, in our simulations, 28.4, 22.1 and 23.4 % (different due to scar morphology), of the core infarcted area was replaced by hPSC-CMs in the small, medium and large scar, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that progenitor cells may stimulate cardiac repair and regeneration by producing wide range of cytoprotective, anti-inflammatory and angiogenesis promoting factors leading to oxidative stress reduction, ventricle remodeling inhibition and recruitment of endogenous progenitor cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%